2018
DOI: 10.3892/ijo.2018.4401
|View full text |Cite
|
Sign up to set email alerts
|

PGC1α promotes cisplatin resistance in human ovarian carcinoma cells through upregulation of mitochondrial biogenesis

Abstract: The induction of lesions in nuclear and mitochondrial DNA by cisplatin is only a small component of its cytostatic/cytotoxic activity. The signaling pathway network in the nucleus and cytoplasm may contribute to chemotherapeutic resistance. Peroxisome proliferator-activated receptor-coactivator 1α (PGC1α)-mediated mitochondrial biogenesis regulates mitochondrial structural and the functional adaptive response against chemotherapeutic stress, and may be a therapeutic target. However, this regulatory network is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…Interestingly, a high mitophagic rate has been reported to be associated with chemoresistance in several cancer cell types (Su et al, 2016;Villa et al, 2017;Yamashita et al, 2017;Naik et al, 2018), and Zheng et al (2015) further observed that mitophagy participates in hypoxia-induced radioresistance in breast cancer cell lines. There is also good evidence that a high rate of mitochondrial biogenesis, primarily depending on activation of mitochondrial transcription factor A (TFAM) and transcription coactivator peroxisome proliferator-activated receptor γ coactivator-1α (PGC-1α), participates in chemoresistance (Gabrielson et al, 2014;Wu et al, 2016;Shen et al, 2018;Hu and Guo, 2019). TFAM and PGC-1α have not yet been linked to radioresistance, but Wang et al (2017) recently showed that silencing mitochondrial single stranded DNA-binding protein (SSBP1), a protein that normally ensures mtDNA stability, decreased mtDNA copy number and sensitized H1299 human lung cancer cells to X-ray irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a high mitophagic rate has been reported to be associated with chemoresistance in several cancer cell types (Su et al, 2016;Villa et al, 2017;Yamashita et al, 2017;Naik et al, 2018), and Zheng et al (2015) further observed that mitophagy participates in hypoxia-induced radioresistance in breast cancer cell lines. There is also good evidence that a high rate of mitochondrial biogenesis, primarily depending on activation of mitochondrial transcription factor A (TFAM) and transcription coactivator peroxisome proliferator-activated receptor γ coactivator-1α (PGC-1α), participates in chemoresistance (Gabrielson et al, 2014;Wu et al, 2016;Shen et al, 2018;Hu and Guo, 2019). TFAM and PGC-1α have not yet been linked to radioresistance, but Wang et al (2017) recently showed that silencing mitochondrial single stranded DNA-binding protein (SSBP1), a protein that normally ensures mtDNA stability, decreased mtDNA copy number and sensitized H1299 human lung cancer cells to X-ray irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…shrna sequences targeting human PGc-1α and a non-target sequence were constructed by Genechem co., ltd. (Shanghai, china. ), as previously described (16). The sequences of PGc-1α shrna and the non-target shrna were 5'-GTT aTa ccT GTG aTG cTT T-3' and 5'-TTc Tcc Gaa cGT GTc acG T-3', respectively.…”
Section: Methodsmentioning
confidence: 99%
“…coverslips were placed in 24-well plates and 8x10 4 cells were added into each well. Mitochondria were stained in live cells using MitoTracker™ red cMXros (invitrogen; Thermo Fisher Scientific, inc.), as previously described (16).…”
Section: Methodsmentioning
confidence: 99%
“…The drug-resistant ovarian cancer cell line, SKOV3/DDP, was bought from the Institute of Cancer Research, Chinese Academy of Medical Sciences (Beijing, China). 19,20 Cell counting kit-8 (CCK-8) and Annexin V-FITC were purchased from Jiamay Biotech (The catalog numbers are AP1008 and LHK601-100, respectively; China). Primary antibodies against FOXO3a or PUMA were purchased from Abcam (The catalog numbers are ab12162 and ab9643, respectively; USA).…”
Section: Methodsmentioning
confidence: 99%